Experimental and numerical study of polyurea coating systems for blast mitigation of concrete masonry walls. (1st June 2023) - Santos, A.P.; Chiquito, M.; Castedo, R.; López, L.M.; Gomes, G.; Mota, C.; Fangueiro, R.; Mingote, J.L.
Highlights: 6 mm thick polyurea layers offer an adequate improvement in retrofitting CMU walls. The polyurea systems can deflect and sustain debris during a blast event. Polyurea coatings do not increase the out-of-plane resistance of the wall. Abstract: A blast event may result in structural damage, generating high velocity fragments that usually come from masonry walls. To reduce the extent of damage from an explosion, one solution is to improve the strength of the structures. This can be achieved by retrofitting. In the field of safety against blast loading, experimental tests are of great value in assessing and understanding the phenomenon and its effects on structures. However, experiments in a blast environment are difficult and expensive to conduct. For that reason, numerical modelling is commonly used as an alternative to experimental testing. In this study, four concrete masonry walls were tested in two different blast trials carried out at full scale; one wall was unreinforced, and the other three were retrofitted with different polyurea coating systems. Additionally, a numerical model using a finite element code was applied to reproduce the experimental tests. The geometric model was created using a detailed micro-modelling approach. To calibrate the simulation, the results between the field test and the numerical model were compared using quantitative and qualitative data. A parametric study was carried out to explore the rupture limits of the polyurea layer. The polyurea coatings that were tested proved to be a good retrofit option for non-load bearing concrete masonry walls. According to the present work, it was found that a thickness of 6 mm provided a satisfactory improvement in retrofitting concrete masonry walls, although a 10-mm thick layer would considerably increase the rupture limit of the polyurea. The numerical modelling method used appears to be an acceptable approach for reproducing blasting tests.